Circulating tumor cells et al.: towards a comprehensive liquid biopsy approach in breast cancer - Eleonora Nicolò; Caterina Gianni; Letizia Pontolillo; Mara Serena Serafini; Laura Muñoz-Arcos; Eleni Andreopoulou; Giuseppe Curigliano; Carolina Reduzzi; Massimo Cristofanilli (2024)
Abstract: Liquid biopsy has emerged as a crucial tool in managing breast cancer (BC) patients, offering a minimally invasive approach to detect circulating tumor biomarkers. Until recently, the majority of the studies in BC focused on evaluating a single liquid biopsy analyte, primarily circulating tumor DNA and circulating tumor cells (CTCs). Despite the proven prognostic and predictive value of CTCs, their low abundance when detected using enrichment methods, especially in the early stages, poses a significant challenge. It is becoming evident that combining diverse circulating biomarkers, each representing different facets of tumor biology, has the potential to enhance the management of patients with BC. This article emphasizes the importance of considering these biomarkers as complementary/synergistic rather than competitive, recognizing their ability to contribute to a comprehensive disease profile. The review provides an overview of the clinical significance of simultaneously analyzing CTCs and other biomarkers, including cell-free circulating DNA, extracellular vesicles, non-canonical CTCs, cell-free RNAs, and non-malignant cells. Such a comprehensive liquid biopsy approach holds promise not only in BC but also in other cancer types, offering opportunities for early detection, prognostication, and therapy monitoring. However, addressing associated challenges, such as refining detection methods and establishing standardized protocols, is crucial for realizing the full potential of liquid biopsy in transforming our understanding and approach to BC. As the field evolves, collaborative efforts will be instrumental in unlocking the revolutionary impact of liquid biopsy in BC research and management.